Pharmacokinetics of NS-105, a Novel Cognition Enhancer - Mukaia, Hideya; Sugimotoa, Taketoshi; Agoa, Masayuki; Morinoa, Akira; Takaichib, Matsuo; Ogawab, Yukihiko; Sekib, Hideaki; Matsuurab, Chizuko; Esumib, Yoshio (Arzneimittelforschung, 1999)
The tissue distribution and transfer into the fetus and milk of NS-105 ((+)-5-oxo-D-proline- piperidinamide monohydrate, CAS 110958-19-5), a novel cognition enhancer, were investi- gated in rats after single oral administration of 14C-NS-105. The effects of repeated oral ad- ministration on the pharmacokinetics of NS-105 and hepatic drug-metabolizing enzyme activ- ities also were investigated in rats.The radioactivity concentration in most tissues of male rats reached a maximum of 0.5 h after the single oral administration of 14C-NS-105, indicating rapid absorption and distribution. 0.5 h after the administration, the highest concentrations were present in the kidney and stomach, and the lowest in the white fat. The concentrations in the remaining tissues were moderately lower than the plasma value. The radioactivity concentrations in all the tissues tested decreased along with the plasma concentration, and were below or near the detection limit 24 h after the administration. Most of the radioactivity in the plasma, liver, kidney and cerebrum was due to unchanged NS-105.The tissue distribution patterns of radioactivity in female (non-pregnant) and pregnant rats after the oral administration of 14C-NS-105 did not differ from the pattern in male rats, reveal- ing neither sex- nor pregnancy-related differences in NS-105 distribution. In pregnant rats, the maximum concentration in the fetus was 66% of that in the maternal plasma. In lactating rats, the radioactivity concentration in the milk was similar to that in the plasma.During and after the repeated oral administration of 14C-NS-105, the plasma concentrations and cumulative urinary and fecal excretions of radioactivity did not change with the number of administrations and were similar to the corresponding values after the single administra- tion. The radioactivity concentrations in most tissues 8 h after the 7th, 14th and 21st adminis- trations were about twice the corresponding values after the single administration, indicating that there is no marked accumulation of radioactivity in the tissues and that a steady state level was reached within 1 week.Repeated oral administration of NS-105 (10 mg/kg) to male rats did not affect hepatic drug-metabolizing enzyme activities.
Keywords: CAS 110958-19-5; Cognition enhancer; NS-105, distribution; pharmacokinetics, rat; repeated administration; (+)-5-Oxo-D-prolinepiperidinamide monohydrate